Relationship between asthma and cognition: the Cooper Center Longitudinal Study. Issue 4 (15th February 2013) - Caldera‐Alvarado, G.; Khan, D. A.; DeFina, L. F.; Pieper, A.; Brown, E. S.
Abstract: Background: Minimal data are available on the relationship between asthma and cognitive performance. In this report, we examine the relationship between asthma and cognitive performance in older adults, a subpopulation with elevated risk of cognitive impairment. Methods: We conducted a cross‐sectional, retrospective analysis of 1380 participants age ≥55 who completed preventive health examinations at the Cooper Clinic in Dallas, TX. Cognition was assessed using the Montreal Cognitive Assessment (MoCA), a brief test for mild cognitive impairment. Data were analyzed in a multiple logistic regression using MoCA scores suggestive of cognitive impairment as the dependent variable. Results: When controlling for demographic characteristics, self‐rated health status, inhaled corticosteroid use, and FEV1 /FVC, asthma were associated with 78% increased risk of cognitive impairment ( P =  0.02) as defined by MoCA score. Conclusions: In the largest sample examined to date, we have identified a significant relationship between asthma and cognitive impairment in older people.